The Judicial Construction of Europe. - Stone Sweet, Alec (Oxford University Press, Incorporated, 2004)
After developing and testing a theory of integration, Alec Stone Sweet assesses the impact of the European Court of Justice on the politics of trade, sex equality, and environmental protection in the European Union.